The Antecedent Variables of Quality of Life among Female Factory Workers - Purba, Sylvia Diana; Sandroto, Christine Winstinindah (Universitas Prasetiya Mulya, 2017)
This study aims to examine the quality of life of female factory workers that is hypothesized as affected by work-family conflict and job satisfaction and moderated by perceived organizational support and labor union support. The respondents of the research are female factory workers who are already married and have children, in which 158 respondents are from Jabodetabek and 66 are from Batam. The result shows that work-family conflict significantly decreases quality of life, and perceived organizational support also has a significant positive moderating effect toward quality of life. The quality of life is affected by job satisfaction and work-family conflict but not moderated by labor union support. This research describes that although the work-family conflict of female factory workers has no influence on job satisfaction but it reduces the quality of life directly with the result that job satisfaction is not an intervening variable.